The association between blood pressure level and serum uric acid concentration in hemodialysis patients - Jamshid Roozbeh; Mohammad-Mahdi Sagheb; Elaheh Vafaie (Society of Diabetic Nephropathy Prevention, 2015)
Background: High blood pressure is a common condition in hemodialysis patients. Uric acid, which is high in these patients due to decreased clearance, had been shown to positively correlate with blood pressure in animal studies. Objectives: The goal of this investigation was to evaluate the impact of high uric acid level on blood pressure in these patients. Patients and Methods: Ninety-one patients, on three times weekly hemodialysis, were studied. Uric acid levels were measured just before and after hemodialysis along with blood pressures before, during and after each session. Data were analyzed by SPSS 15. A P value less than 0.05 was considered significant. Results: 40 (44%) of patients had serum uric acid ≥6 mg/dl. Before dialysis 51 (61%) and 19 (21%) had high systolic blood and diastolic blood pressures respectively. Also, 50 (55%) were with wide pulse pressure and 63 (69%) had high mean arterial pressure (MAP). Additionally 62 (68%) developed inter-dialysis hypotension. After measuring odds ratio for hyperuricemia in each group, we observed low risk of hypruricemia in the group with high systolic pressure (OR = 0.352; 95% CI: 0.147-0.844; P = 0.01), the high MAP group (OR = 0.382; 95% CI: 0.153-0.955; P = 0.03) and wide pulse pressure group (OR = 0.416; 95% CI: 0.177-0.975; P = 0.04). There was no association between high uric acid level and diastolic pressure (P = 0.11) and inter-dialysis hypotension (P = 0.33). No relationship was found between serum uric acid and KT/V (P = 0.2), normalized protein catabolic rate (nPCR) (P = 0.07) and body mass index (BMI) (P = 0.4). Conclusions: This study showed paradoxical association between high uric acid level and high systolic pressure, high MAP and wide pulse pressure and these effects were independent of dialysis duration, dialysis efficacy and nutrition, assuming that these relationships could be due to reverse epidemiology in dialysis patients.